The Afterlife of the Roman de la rose - McWebb, Christine (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2021)
Mobility in learned circles was a reality in the Europe of the Middle Ages, and it is only when we consider the reception of well-known works, such as the thirteenth-century Roman de la rose, in the countries where they circulated in the local language that we are able to gain a more complete understanding of their impact on literary and cultural currents even after the authors had passed away. Guillaume de Lorris and Jean de Meun’s conjoined Roman de la rose (1236, 1269-78) is without a doubt one of the foundational works of French medieval literature with over 360 extant manuscripts. Focusing on two non-French adaptations of this work that appeared within a century of the date of its composition, I show that these translations, or more accurately rewritings, enabled its survival and contributed to its sustained popularity in medieval Europe. The adaptations that are the subject of this analysis are Il Fiore, a thirteenth-century translation and adaptation into Italian often attributed to Dante, and the Romaunt of the Rose, commonly attributed to Geoffrey Chaucer. I conclude that through the medieval practice of interpretatio, the authors of the Fiore, and the Romaunt of the Rose adapt the original text to reflect their own contemporary cultural realities.